2020
DOI: 10.1155/2020/6131485
|View full text |Cite
|
Sign up to set email alerts
|

Predictive and Prognostic Factors of Synchronous Colorectal Lung-Limited Metastasis

Abstract: Aim. This study is aimed at investigating predictive and prognostic factors of synchronous colorectal lung-limited metastasis (SCLLM) based on The Surveillance, Epidemiology, and End Results (SEER) database. Methods. A multivariate logistic regression model was constructed to identify independent predictors of SCLLM. A multivariate Cox proportional hazards regression model was used to distinguish independent prognostic factors. Results. This study enrolled 168,007 colorectal cancer (CRC) patients without metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
(13 reference statements)
1
4
0
Order By: Relevance
“…Radical surgery including lymphadenectomy of CRC is a decisive factor for prognosis and is necessary for the therapeutic staging of the patient, the minimum number of 12 examined lymph nodes has been accepted in clinics since 1990 31 . We found that the identification of fewer than 12 regional nodes was associated with a worse CSS, which was consistent with many studies 20 , 32 . In particular, the role of primary tumor resection in CRC patients with distant metastases remains controversial.…”
Section: Discussionsupporting
confidence: 92%
“…Radical surgery including lymphadenectomy of CRC is a decisive factor for prognosis and is necessary for the therapeutic staging of the patient, the minimum number of 12 examined lymph nodes has been accepted in clinics since 1990 31 . We found that the identification of fewer than 12 regional nodes was associated with a worse CSS, which was consistent with many studies 20 , 32 . In particular, the role of primary tumor resection in CRC patients with distant metastases remains controversial.…”
Section: Discussionsupporting
confidence: 92%
“…Our previous research explored the prognostic factors of colorectal liver-limited and lung-limited metastasis, that were inconsistent between the two groups [24,25]. Similarly, T staging can be used as a prognostic factor for rectal lung-limited metastasis but not for rectal liver-limited metastasis in this study (Table S3).…”
Section: Discussionmentioning
confidence: 85%
“…Approximately 60% of OC patients were determined at an advanced stage. Previous studies reported that the invasion of OC cells mainly depends on the hematogenous circulation and lymphatic channels [2], and pulmonary metastases in OC always are classified at a lower-level outcome that notably leads to a poor prognosis [3,4]. As the second most common distant metastatic site, the morbidity of lung metastasis (LM) ranges from 6% to 16% [5][6][7][8].…”
Section: Ivyspring International Publishermentioning
confidence: 99%